Four irradiation and three positioning techniques for whole‐breast radiotherapy: Is sophisticated always better?. Issue 11 (15th September 2022) - Schoepen, Max; Speleers, Bruno; De Neve, Wilfried; Vakaet, Vincent; Deseyne, Pieter; Paelinck, Leen; Van Greveling, Annick; Veldeman, Liv; Detand, Jan; De Gersem, Werner
Abstract: Purpose: We report on a dosimetrical study of three patient positions (supine, prone dive, and prone crawl) and four irradiation techniques for whole‐breast irradiation (WBI): wedged‐tangential fields (W‐TF), tangential‐field intensity‐modulated radiotherapy (TF‐IMRT), multi‐beam IMRT (MB‐IMRT), and intensity‐modulated arc therapy (IMAT). This is the first study to evaluate prone crawl positioning in WBI and the first study to quantify dosimetrical and anatomical differences with prone dive positioning. Methods: We analyzed five datasets with left‐ and right‐sided patients ( n  = 51). One dataset also included deep‐inspiration breath hold (DIBH) data. A total of 252 new treatment plans were composed. Dose–volume parameters and indices of conformity were calculated for the planning target volume (PTV) and organs‐at‐risk (OARs). Furthermore, anatomical differences among patient positions were quantified to explain dosimetrical differences. Results: Target coverage was inferior for W‐TF and supine position. W‐TF proved overall inferior, and IMAT proved foremost effective in supine position. TF‐IMRT proved competitive to the more demanding MB‐IMRT and IMAT in prone dive, but not in prone crawl position. The lung‐sparing effect was overall confirmed for both prone dive and prone crawl positioning and was largest for prone crawl. For the heart, no differences were found between prone dive and supine positioning, whereas prone crawl showed cardiac advantages, although minor compared to the established heart‐sparing effect of DIBH. Dose differences for contralateral breast were minor among the patient positions. In prone crawl position, the ipsilateral breast sags deeper and the PTV is further away from the OARs than in prone dive position. Conclusions: The prone dive and prone crawl position are valid alternatives to the supine position in WBI, with largest advantages for lung structures. For the heart, differences are small, which establishes the role of DIBH in different patient positions. These results may be of particular interest to radiotherapy centers with limited technical resources.